A Web-Based Multidomain Lifestyle Intervention for Older Adults: The eMIND Randomized Controlled Trial - de Souto Barreto, Philipe (J Prev Alzheimers Dis, 2020)
IMPORTANCE/OBJECTIVE: To describe the feasibility and acceptability of a 6-month web-based multidomain lifestyle training intervention for community-dwelling older people and to test the effects of the intervention on both function- and lifestyle-related outcomes. DESIGN: 6-month, parallel-group, randomized controlled trial (RCT). SETTING: Toulouse area, South-West, France. PARTICIPANTS: Community-dwelling men and women, ≥ 65 years-old, presenting subjective memory complaint, without dementia. INTERVENTION: The web-based multidomain intervention group (MIG) received a tablet to access the multidomain platform and a wrist-worn accelerometer measuring step counts; the control group (CG) received only the wrist-worn accelerometer. The multidomain platform was composed of nutritional advices, personalized exercise training, and cognitive training. MAIN OUTCOMES AND MEASURES: Feasibility, defined as the proportion of people connecting to ≥75% of the prescribed sessions, and acceptability, investigated through content analysis from recorded semi-structured interviews. Secondary outcomes included clinical (eg, cognitive function, mobility, health-related quality of life (HRQOL)) and lifestyle (eg, step count, food intake) measurements. RESULTS: Among the 120 subjects (74.2 ± 5.6 years-old; 57.5% women), 109 completed the study (n=54, MIG; n=55, CG). 58 MIG subjects connected to the multidomain platform at least once; among them, adherers of ≥75% of sessions varied across multidomain components: 37 people (63.8% of 58 participants) for cognitive training, 35 (60.3%) for nutrition, and three (5.2%) for exercise; these three persons adhered to all multidomain components. Participants considered study procedures and multidomain content in a positive way; the most cited weaknesses were related to exercise: too easy, repetitive, and slow progression. Compared to controls, the intervention had a positive effect on HRQOL; no significant effects were observed across the other clinical and lifestyle outcomes. CONCLUSIONS AND RELEVANCE: Providing multidomain lifestyle training through a web-platform is feasible and well-accepted, but the training should be challenging enough and adequately progress according to participants’ capabilities to increase adherence. Recommendations for a larger on-line multidomain lifestyle training RCT are provided.